When religion hurts you : healing from religious trauma and the impact of high-control religion - Anderson, Laura E., 1982- (Brazos Press, a division of Baker Publishing Group, 2023)
"Drawing on clinical research, stories from clients, and her own experience, an expert on religious trauma shows how readers can live as healing individuals after leaving a high-demand, high-control religious system"--